TINJAUAN TEOLOGIS PEMUGARAN MAKAM DI DESA TANJUNG RIU - Susanto, Deri (Dharma Duta, 2022)
The restoration of graves in the GKE congregation in Tanjung Riu Village, also known as secondary burials, is almost similar to the secondary burial of the Ngaju Dayak people who are Kaharingan Hindus, which is called the tiwah ceremony. Tanjung Riu GKE congregation offers an alternative cultural choice (tomb restoration) amidst the established culture, namely tiwah. The practice of restoring tombs became problematic when it was accused by some priests from the Kalimantan Evangelical Church (GKE) of being a form of syncretism. In order not to fall into syncretism, there needs to be a theological review that must bear two models of cross-cultural mission or two options together; This means that the ritual of tomb restoration must show loyalty to the Bible and at the same time be culturally relevant without falling into dualism, namely syncretism and relativism. The research findings show that there is a clash of understanding between the congregation and the church, between theocentric and totalitarian understandings, and while the congregation sees God in the restoration of the tomb as a form of naturalistic theism, it is only suitable in terms of the congregation's immanence.